Observation of relaxation of molecular spins in CH4 and CD4 crystals in thermal conductivity experiment: Classical Cryocrystals - Pisarska, Elwira; Stachowiak, Piotr; Jeźowski, Andrzej (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2007)
The paper reports preliminary results on the kinetics of the molecular spin conversion in solid methane (CH4) and deuterated methane (CD4), obtained through thermal conductivity measurements in the temperature range 2–10 K.